Dislokasi Identitas Agama dan Budaya Perkotaan: Perkembangan Kampung Wisata di Kota Yogyakarta - Prasojo, Zaenuddin Hudi; Arifin, Muhammad; Abdullah, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2020)
Since the early 20th century, villages in the city of Yogyakarta has started to become villages of tourism following the government promoting tourism in the region. Originally carrying local and cultural identities, those villages appear to be touristic, accommodating the needs of the visitors. This work attempts to explore how this social phenomenon happening to two urban villages within the city namely Kampung Kauman and Kampung Prawirotaman. It focuses on explaining how the villagers actively play their roles in the neighborhood in social and cultural processes within the new environment and physical space. Â The appropriate data found in the field is analyzed accordingly to the research questions by employing a qualitative approach. Â The work suggests that cultural identity has changed in these two urban villages as a result of the influence of external values promoting the redefinition and redesign of public and social space. Besides, it also finds that delegitimization of the identity of Kampung and communality dislocation has occurred due to tourism purposes. The new formulation of the Kampung does not only reflect the emergence of new ideology and tradition but also stimulate resistance, conflict, and negotiation. This study recommends the importance of mentoring programs from the strategic stakeholders for better space and cultural transformation leading to the prevention of the damage of local wisdom basis within urban communities.